RESIKO MORAL HAZARD PADA PERBANKAN SYARIAH DI INDONESIA - Rina Mandara Harahap (Fakultas Syariah (Syari'ah Faculty ), 2016)
The problems of Principal-Agent often occurred in financing scheme of Islamic banking as the effect of imbalance information between Shahibul Maal and Mudharib are adverse selection and moral hazard. Providing adequate information and determining optimum sharing schemethat meet the utility of Islamic banking and client can reduce the problem of adverse selection and moral hazard. Even though financial product is highly risked, yet it can be reduced by optimizing sharing scheme and thus the financial amount can be increased. Furthermore, the effective supervision of the corporation as a control management is necessary to minimize financial risk. Then, Good Corporate and Good Governance (GCG) Principles must be implemented in Islamic banking as a consequence of public responsibility in running the bank according to shariah principle based on Al-Qur’an, Hadith, and Ijmā